Dispersion and failure analysis of PLA, PLA/GNP and PLA/CNT-COOH biodegradable nanocomposites by SEM and DIC inspection. (January 2017) - Pinto, V.C.; Ramos, T.; Alves, A.S.F.; Xavier, J.; Tavares, P.J.; Moreira, P.M.G.P.; Guedes, R.M.
Abstract: Biodegradable polymers such as PLA have been studied for medical applications, human ligament repair is one of such cases. However, these materials can be applied in other sectors as aerospace, aeronautics, automotive, food packaging. PLA presents a relatively brittle on the mode I fracture behavior, being often blend with other biodegradable or non-degradable polymers to improve its fracture energy. For some existing applications, PLA components exhibit accumulated permanent deformation resulting from dynamic mechanical inputs, resulting on failure by laxity of parts. Aiming the improvement of PLA mechanical properties, the inclusion of carbon nanofillers into PLA matrix, in particular, CNT-COOH and GNP have been developed, due to their strong sp2 carbon-carbon bondings and their geometric arrangement that enhance mechanical properties of the polymer matrix. PLA and nanocomposites were produced by melt blending followed by compression moulding in a hot press, with small weight percentages of nanofillers added to the matrix. Nanocomposites dispersion was evaluated by SEM. Quasi static tensile tests were performed on a mechanical testing machine (Instron™ ElectroPuls E1000) along with strain field measurements of specimens with centred crack with digital image correlation, revealing strain distribution along specimens. Highlights: PLA/CNT-COOH and PLA/GNP were produced successfully by melt blending. Nanocomposites dispersion was evaluated by SEM. Carbon nanostructures were perfectly embedded, despite some reduced agglomerates. Strain fields were obtained with DIC on static tensile tests. PLA/GNP2 presented the less uniform strain field (fragile points of rupture).